Gravitational separation of 137Cs contaminated soil in Fukushima environment: Density dependence of 137Cs activity and application to volume reduction. (May 2022) - Yamasaki, Shinya; Saito, Hikaru; Nakamura, Tsukasa; Morooka, Kazuya; Sueki, Keisuke; Utsunomiya, Satoshi
Abstract: Behavior of radiocesium in Fukushima after its deposition is mainly controlled by mobility of soil components, of which the density is one of the parameters governing the mobility; however, little information is available on the density of soil components associated with radiocesium in environment. Furthermore, the reduction of the volume of radiocesium-contaminated soil in the interim storage is highly demanded. In this study, we developed a gravitational separation method using a sodium polytungstate (SPT) solution combined with size fractionation to understand the relation between 137 Cs activity and the density of surface soil components and evaluate the feasibility of the method for the volume reduction of the contaminated soil. In all soil samples examined, 137 Cs concentration of the small size (<0.063 mm) and high-density (2.4–2.8 g cm −3 ) fraction was the highest among the separated fractions, whereas most of the radiocesium-rich micro-particles were distributed in the small size (<0.063 mm) and low density (<2.4 g cm −3 ) fraction. Although ultrasonication improved the size separation efficiency, a single-step gravitational separation method using an SPT solution with a density of 2.4 g cm −3 without size separation and ultrasonication revealed that the 137 Cs concentration on 50°C-dry weight basis in the dense (>2.4 g cm −3 ) fraction was 25.6–82.7% lower than that of the bulk sample for all soil samples. In particular, for the samples with a bulk 137 Cs concentration of 29.6 Bq g −1 50°C-dry weight, the 137 Cs concentration in the fraction was below the safety treatment requirement (i.e., 8 Bq g −1 ). Therefore, single-step gravitational separation may be used for the volume reduction of contaminated soils. Highlights: Size separation and gravitational separation were applied to contaminated soil in Fukushima. The ultrasonication of the sample resulted in a considerable shift in the gravitational separation values. The highly radioactive particles were mainly included in the dense (2.4–2.8 g cm −3 ) and small (<0.063 mm) fraction. Radiocesium-rich micro-particles were divided into the coarse (<2.4 g cm −3 ) and small fraction (<0.063 mm).